ESTIMATION OF POLLUTANTS EMISSION RATE FROM ACTIVITY OF ISFAHAN CITY TAXIES - Zeinab Eskandari; Amirreza Talaiekhozani; Golshan Makipoor; Saeed Jafari; Shahabaldin Rezania (Journal of Air Pollution and Health, 2018)
Introduction: Determining the sources of air pollutants and the emission rate from each one is the most important bases for the air pollution control policy in cities. The aim of this study was to determine the amount of different pollutants emission caused by urban taxies in Isfahan. Materials and methods: In the first step, information was gathered about the number of active taxies, type of vehicle, manufactured year and the type of fuel consumed in Isfahan from taxi management and supervision organization. In the next step, by referring to the vehicle’s manual, the used technology to design and build their engines was collected. Finally, the gathered information was introduced to International Vehicle Emission (IVE) model to analyze. Results: Based on the results, the total emitted pollutants into Isfahan atmosphere was estimated as 16,276 tons of carbon dioxide, 78 tons of methane, 153 tons of carbon monoxide, 8.67 tons of volatile organic compounds, 25.69 tons of nitrogen oxides and 0.036 tons of sulfur oxides per year. This study confirmed that thousands of tons of volatile organic compounds, carbon dioxide, nitrogen oxides and sulfur oxides are introduced into the atmosphere by Isfahan taxies. Conclusions: Although, the values of pollutants emission were very high, the number of passenger-to-car ratio in taxis is too much higher than that of single- person private cars.